Design of a product by cold forging / Daneil Awan, Jalani Embik and Roy Hannis - Awan, Daneil; Embik, Jalani; Hannis, Roy (1997)
Cold extrusion is a special type of forging process wherein cold metal is forced to flow plastically under compressive force into a variety of shapes. These shapes are usually axisymmetric with relatively small nonsymmetrical features, and unlike impression die forging, the process does not generate flash. The terms " cold forging " and " cold extrusion " are often used inter changeable and refer to well-known forming operations such as extrusion, upsetting or heading, coining, ironing and swaging. These operations are usually performed in mechanical or hydraulic presses, several forming steps are used to produce a final part of relatively complex geometry, starting with a slug or billet of simple shape. Through a combination of these techniques, a very large number of parts can be produced.